Cocaine use modifies the association of antiretroviral therapy regimens with obesity in HIV-infected adults. (December 2019) - Li, Ji; Lai, Hong; Chen, Shaoguang; Lai, Shenghan
Abstract: Aims: Although evidence suggests that antiretroviral therapy (ART) use may contribute to obesity in individuals with HIV infection, the alleged association between ART use and obesity in HIV-infected patients remains controversial due to differences in patient characteristics and study designs. Additionally, cocaine is commonly used among those with HIV infection and may affect body weight. The main objective of this study was to examine the interactive effects of ART regimens and cocaine use on obesity in adults with HIV infection. Methods: Between 2003 and 2014, 672 HIV-infected study participants who resided in Baltimore, Maryland, were enrolled in a study investigating HIV/ART-associated comorbidities. Robust linear regression and multiple logistic regression models were conducted to examine whether cocaine use modified the association between antiretroviral drugs and body weight status. Results: Adjusted regression analyses showed that duration of protease inhibitor use was significantly associated with lower BMI (β = −0.012, SE = 0.005, p < 0.05) and a reduced risk of obesity (OR = 0.313, 95% CI = 0.135, 0.724) in cocaine non-users, while no such association was found in cocaine users. Conclusions: Our findings suggest that reducing cocaine use may alleviate ART-associated weight gain in adults with HIV infection.